Vascular endothelial growth factor (VEGF) and interleukin-1 receptor antagonist (IL-1Ra) as promising biomarkers for distinguishing active from latent tuberculosis in children and adolescents. (May 2022) - Martins, Camila de Paula; Carvalho, Fabiana Rabe; Faustino, Renan; Medeiros, Thalia; Rosário, Natalia Fonseca do; Schmidt, Christiane Mello; Barbosa, Ana Paula; Quintanilha dos Santos, Ana Paula; Pluvier Duarte Costa, Caio; Kegler dos Santos, Hugo Henrique; Yuriko Yaginuma, Karina; Costa da Silva, Elisangela; et al.
Abstract: Since distinguishing pulmonary (PTB) from latent tuberculosis (LTBI) in pediatric patients remains a challenge, we aimed to investigate the efficacy of immune mediators in diagnosing PTB and LTBI in this population. In this cross-sectional study performed with children and adolescents, serum levels of 20 biomarkers were assessed and data were analyzed according to age groups. We included 65 participants (PTB, n = 28 and LTBI, n = 37). Overall, levels of TNF-α, IL-1Ra, IL-6, IL-17A, VEGF, MMP-1, and procalcitonin were significantly higher (P < 0.05) in adolescents and children <10 years-old with PTB. Also, principal component analysis (PCA) showed that immune mediators were able to distinguish PTB from LTBI. VEGF and IL-1Ra presented the highest area under the curve (AUC) values, both separately (AUC 0.890 and 0.785) and combined (AUC 0.99). Taken together, we showed that VEGF and IL-1Ra are promising biomarkers to distinguish PTB from LTBI in pediatric patients, especially in children <5 years-old. Highlights: Diagnosing pulmonary and latent tuberculosis (PTB/LTBI) in children is a challenge. Children with PTB showed higher levels of immune mediators. VEGF and IL-1Ra are promising biomarkers to and distinguish PTB from ILTB.